In search of the key to Ukraine’s success at world markets - O.O.; K.V.; K.V. (Економіка, управління та адміністрування)
The article conducts the analysis of Ukraine’s position among the EU countries in terms of readiness for future production (by components: complexity and structure of production and drivers: human capital and sustainable development resources) for determining the Ukraine’s potential competitiveness in the process of European integration and outlining possible ways of its increasing. The study uses general scientific methods of cognition, systematization and comparison, analysis and synthesis, in particular. During the study, each components of the aggregate indicator of Ukraine’s readiness for the future production has been analyzed in the comparative aspect (by components: complexity and structure of production and drivers: human capital and sustainable development resources); urgent issues for increasing the competitive advantages of Ukraine at the world markets and its ability to counter risks and challenges resisting are identified, the directions of further researches are outlined. The theoretical significance of the study consists in the development (increasing) of scientific knowledge about the factors of country’s readiness to counter risks and challenges of the globalized world future and their impact on Ukraine’s competitiveness. The practical significance of the study results is the possibility of using the markers of the gaps in Ukraine’s readiness by Government of Ukraine, the scientific community and non-governmental organizations for developing a strategy and its tools for increasing Ukraine’s indicators to reference values of the EU member states. The scientific novelty of the research is in developing an approach to identifying Ukraine’s competitive advantages at world markets through comparative analysis of EU members selected indicators in view of future risks and challenges.